Political elite behavior effectiveness in combating the COVID-19 pandemic: A case study of Vietnam - Tran, Huong Thi (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
The article aims to develop an empirical approach to identifying the key factors in the political elite behavior effectiveness in combating the COVID-19 pandemic propagation exemplified by Vietnam. Using regression analysis and the Chow test, we identified key behavioral factors that affect the effectiveness of the fight against the COVID-19 pandemic in terms of mortality rates and the state of the economy. The study sample was formed by data from 67 countries worldwide for 2020. The results suggest that the Rule of Law significantly influences the state of the economy in a pandemic. The COVID-19 mortality rate is affected by the Global Health Security Index, gender, and cultural factors. Based on the constructed linear multivariate regression models, we calculated the contribution of significant factors to the effectiveness of combating the pandemic in Vietnam, their stimulating and de-stimulating effects compared to the average values of these indicators for the sample countries.